Сalculation of electrical conductivity of a superionic conductor - Рахымбеков, А (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The possibility of analytic determination of the type of conductivity of electric current by a solid oxide ionic conductor based on stabilized zirconium dioxide (solid electrolyte, superionic) under the influence of a direct current electric field and high temperature in the range of 500 0 -900 0 degrees is considered The objectives of the study of this work are in the mathematical interpretation of the phenomenal phenomenon of substance transfer and irreversible changes in the solid oxide electrolyte (or superionics) of the oxygen concentration cell, with mixed electrolyte conductivity. The connection with the need to expand the temperature range of application of the method and the range of the studied ceramic materials is shown. It is confirmed that the sample has mixed conductivity, bound to O 2− anions, Me + cations, and electrons with nonzero concentrations n a,k,e charges q a,k,e and mobilities in the field of electric forces. A mathematical formula for determining the mobility of anions and cations in a solid oxide superionic conductor based on stabilized zirconium dioxide has been derived.